Optimized Factory Layout Design for Enhanced Productivity and Quality: A Case Study on Aerokit Painting - Ismail, Mohd Fauzi; Adull Manan, Nor Fazli; Abdul Hamid, Nor Hissham; Mahamad Basri, Mahamad Hisyam (Journal of Advanced Industrial Technology and Application, 2026)
In automotive production, the improvement in production effectiveness and quality while containing costs is essential. This research examines the painting process in an automotive plant in Malaysia that suffered from low throughput rates, high defect levels, and an overworked quality control section. To remedy these issues, the layout of the factory was transformed into a U-shaped layout incorporating Lean Manufacturing values, Statistical Process Control (SPC), and real-time Power BI monitoring. The interventions improved the flow of material, decreased operator walking distances, and added in-process quality checks in addition to operator self-audits. Installation of these measures yielded a 33% increase in production volume, an 80% defect per vehicle reduction (DPV), and a 47% reduction in takt time. The results show the effectiveness in combining Lean values with digital monitoring and offer a real-world model for the enhancement of quality and productivity in automotive painting operations.